The Development of Health Behavior Modification Model in Non-communicable Chronic Diseases Risk by Using Participatory Approach in Knowledge Management of the Community in Banwangthong Bangmulnak District, Phichit Province - Chotigakham, Thanee (Journal of Disease and Health Risk DPC.3, 2023)
The two aims of this research were to develop a behavior change model for improving the health behaviors of the non-communicable disease (NCD) population at risk and to assess the effectiveness of the health behavior change intervention based on the PRECEDE Model. The research is conducted as an operational study, divided into qualitative research using tools such as interviews with 10 health behavior change leaders and a survey questionnaire administered to 40 individuals at-risk of participating in health behavior change activities. The qualitative data was analyzed by observing the involvement in knowledge management, including the contextual background, collaborative planning, implementation, and evaluation. The quantitative analysis involves a health status and health behavior survey, analyzed using descriptive statistics, paired t-tests for inferential statistics, and Pearson correlation analysis. The research findings indicate that: 1) the health behavior change model implemented in the Wang Thong community through knowledge management, community contextual study, and community stimulation had raised community awareness and potential for collaborative health behavior change; and 2) the health behavior change activities had resulted in improved self-efficacy, self-control, and health behaviors among the at-risk group, as well as reduced body mass index, waist circumference, and blood sugar levels, along with decreased blood pressure. The factors contributing to the success of the intervention depend on the participation of all stakeholders in community health care, the leadership capacity, and the team's involvement. Furthermore, policy development and health promotion are essential for accessing health promotion activities.